Ivermectin: pharmacology and therapeutic applications - Chhaiya, Sunita B.; Mehta, Dimple S.; Kataria, Bhaven C. (International Journal of Basic & Clinical Pharmacology, 2017)
Ivermectin is an antiparasitic drug with a broad spectrum of activity, high efﬁcacy as well as a wide margin of safety. It belongs to the family of avermectins. It binds to glutamate-gated chloride iron channels, which are present in invertebrate nerve and muscle cells, and causes the paralysis and death of the parasite. Ivermectin is approved by the US Food and Drug Administration, and used worldwide to treat patients with onchocerciasis and strongyloidiasis. It is also used against a wide range of endoparasites (nematodes) and ectoparasites (insects, acarine) of animals and humans.